Improving The Environmental Performance of The Building Through Biomimicry – Appling study on economic housing in Nasser city, west of Asyut – Egypt –: تحسين الأداء البيئي للمبنى من خلال محاكاة الطبيعة – دراسة تطبيقية على الإسكان الاجتماعي بمدينة ناصر غرب أسيوط – مصر – - Amira Medhat Ibrahim Mahmoud Gouda, Asmaa Nasr Elden Elbadrawy, Lamis Saad Elden Mohamed Elgezawy (Journal of engineering sciences and information technology, 2020)
Despite the development taking place in architecture to the present day, this development had its advantages and disadvantages; With this development, interest in achieving Financial profit to the extent that neglected the humanitarian aspects of the users in spaces, especially climatic aspects, so that the modern buildings represent a thermal burden on the user; Therefore one of the most important challenges facing the designer is how to create an internal environment that achieves thermal comfort for users as well as reduce energy consumption; Therefore, the study aims to reach an environmental strategy to improve the environmental performance of buildings, especially in hot regions, by simulating biological systems to adapt to the environment in plants that live in hot regions and transform them into strategies and environmental elements that contribute to reducing thermal loads within building spaces ;This comes through applying the direct biomimicry method of nature on the cactus plant, which grows in desert areas and can achieve a balance between natural light and heat to increase water storage in addition to its ability to self-shading and self-ventilating, thereby reducing the effect of heat from solar radiation; A model for economic housing has been chosen, the city is "Nasser" in the western of Asyut region, one of the fourth generation cities, and the first in Upper Egypt, as it represents an explicit model for the hot desert environment that needs special treatments to make sustainable buildings that can be compatible with its surrounding environment, By comparing the results of the study to the values of the thermal transfer coefficient of the walls and ceilings in the building before and after the natural simulation process, we find that it decreased by a large percentage, reaching 88% in the walls and 64% in the ceilings, and these ratios help in reducing the rate of thermal loads, which have a role in improving the environmental performance of the building Therefore, the study recommends the necessity of applying nature simulation approaches and making use of methods of dealing with them in order to solve environmental problems in an innovative way.